Study Habits and Academic Performance of Junior High School Pupils in Akuapem South District of Ghana: Implications for Educational Practice - Joyce Aboagyewaa Kwakye; Vera Arhin; Peter Brown (International Journal of Social Sciences & Educational Studies, 2020)
Concerns raised about poor academic performance of pupils in the Akuapem south district, initiated the need to investigate the relationship between five study habit indicators and academic performance of junior high school pupils in the district. A total of 302 JHS pupils in the Akuapem south district were sampled to participate in the study. A study habit inventory developed by Essuman was adapted and used for data collection. An average of pupils three terms academic results was used to measure academic performance. The data collected was analysed using means, standard deviation, Pearson Product Moment correlation coefficient and Regression. The findings of the study revealed that all the five indicators of study habits: time management (b = 1.575, t = 9.175, p <. 001), reading and concentration (b =1.369, t = 8.419, p <.001), notetaking (b = 1.247, t = 7.702, p <.001), assignment and homework (b =1.503, t = 8.671, p <.001) and preparing for examination (b = 1.299, t = 8.225, p <. 001) were positive correlates of academic performance of respondents. The study concluded that good study habits are essential ingredients for better academic performance. The study recommends that teachers and guidance and counselling coordinators at the various basic schools should help pupils with basic skills on how to study. Further, periodic workshops should be organised for teachers on how to assist pupils to acquire good study habits.